Insolvency and Biased Standards - The Case for Proportional Liability - Alexander Stremitzer; Avraham Tabbach (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2009)
We analyze liability rules in a setting where injurers are potentially insolvent and where negligence standards may deviate from the socially optimal level. We show that proportional liability, which sets the measure of damages equal to the harm multiplied by the probability that it was caused by an injurer's negligence, is preferable to other existing negligence-based rules. Moreover, proportional liability outperforms strict liability if the standard of due care is not set too low. Our analysis also suggests that courts should rely on statistical evidence and bar individualized causal claims that link the harm suffered by a plaintiff to the actions of the defendant. Finally, we provide a result which might be useful to regulators when calculating minimum capital requirements or minimum mandatory insurance for different industries.
urn:nbn:de:bvb:19-epub-13265-1
Keywords: K13; 330; judgment proof problem; uncertain causation; court error and misperception; proportional liability; disgorgement